Error Analysis for Digital Beamforming Synthetic Aperture Radars: A Comparison of Phased Array and Array-Fed Reflector Systems - Huber, Sigurd; Younis, Marwan; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2021)
Modern synthetic aperture radar (SAR) systems for Earth observation from space employ innovative hardware concepts. The key idea is to digitize the output of a multielement antenna almost immediately after the receiver and to dynamically process these data either onboard the radar satellite in real time or on the ground. This article addresses the performance of such digital beamforming (DBF) systems in the presence of phase and magnitude errors in the digital channels. For this, analytic expressions for the sensitivity and range ambiguity performance are derived. These equations are kept general so that they are valid for both planar array antennas and array-fed reflector antennas. It is an important objective of this article to compare these two antenna types to each other. A major conclusion from this analysis is that direct-radiating phased arrays are inherently more susceptible to random phase and magnitude errors compared with array-fed reflector antenna-based systems. This manifests itself in a more rapid degradation of the imaging performance with phased array antennas.
Created from Fastlane, Scopus look-up
Keywords: Array-fed reflector; digital beamforming (DBF); error analysis; phased array; synthetic aperture radar (SAR)